Political Meanings, Identity Theory and the History of Ideas: Introducing the Issue - Daria B. Kazarinova; Aleksandr A. Shirinyants (RUDN Journal of Political Science)
The issue of the journal is devoted to a wide range of issues related to the history of ideas, identity issues, the multipolarity of the world, as well as the translation of value meanings and socio-cultural divisions. The articles consider the key aspects of the formation and development of various ideological trends, their impact on modern social processes and cultural transformations. Special attention is paid to the issues of identity at both the individual and collective levels, the analysis of the mechanisms of its construction and its role in the context of globalization. The problems related to the multipolar structure of the modern world, where various political, economic and cultural systems coexist, are also discussed. An important place is occupied by research on the topic of translation of value-semantic narratives, which reveal the mechanisms of transmission of cultural values through generations and between different social groups. The issues of socio-cultural divisions and value splits are considered, which allows for a deeper understanding of the causes of conflicts and tension in modern society. The materials of the issue are of interest to researchers in the field of philosophy and history of politics, specialists in the field of identity studies, as well as for anyone who seeks a deeper understanding of modern social processes and challenges.